Soil structure as an indicator of soil functions: A review - Rabot, E.; Wiesmeier, M.; Schlüter, S.; Vogel, H.-J. (Geoderma, 2018)
Since many processes in soil are highly sensitive to soil structure, this review intends to evaluate the potential of observable soil structural attributes to be used in the assessment of soil functions. We focus on the biomass production, storage and filtering of water, storage and recycling of nutrients, carbon storage, habitat for biological activity, and physical stability and support. A selection of frequently used soil structural properties are analyzed and discussed from a methodological point of view and with respect to their relevance to soil functions. These are properties extracted from soil profile description, visual soil assessment, aggregate size and stability analysis, bulk density, mercury porosimetry, water retention curve, gas adsorption, and imaging techniques. We highlight the greater relevance of the pore network characterization as compared to the aggregate perspective. We identify porosity, macroporosity, pore distances, and pore connectivity derived from imaging techniques as being the most relevant indicators for several soil functions. Since imaging techniques are not widely accessible, we suggest using this technique to build up an open access “soil structure library” for a large range of soil types, which could form the basis to relate more easily available measures to pore structural attributes in a site-specific way (i.e., taking into account texture, soil organic matter content, etc.). •Structural properties are discussed with respect to their relevance to soil functions.•Pore network characterization is more powerful than analyzing disturbed aggregates.•We identified porosity, macroporosity, pore distances, and pore connectivity.•Imaging instruments appeared to be the most reliable tools to measure them.•We suggest developing an open access “soil structure library”.